PARTISIPASI UMAT DALAM LITURGI DI PAROKI SANTO PETRUS DAN PAULUS KABANJAHE - Ginting, Pelta; Simbolon, Erikson (STP St. Bonaventura Medan, 2023)
This research was conducted to determine the participation of the people in liturgical celebrations at the Berastepu Station, St. Petrus and Paulus Parish, Kabanjahe. The research methodology used in this research is qualitative. Data collection techniques are carried out by observation, interviews, and documentation. Data processing techniques are carried out by data reduction, data analysis, and drawing conclusions. The place of research is at Berastepu Station, St. Peter and Paulus Parish, Kabanjahe. The number of informants for this study were 15 people. The findings of this study are that the people's appreciation of the Church's liturgy is still very low. This low appreciation is evident in the participation of the people in the liturgy which is still passive